The Relationship Between Work Engagement, Perceived Organizational Support and Organizational Citizenship Behaviour in Zun Utara Industry Sdn. Bhd. - Chan, Say Yeu (2014)
The purpose of this study is to identify the correlation between work engagement and perceived organizational support (POS) towards organizational citizenship behavior (OCB) at Zun Utara Industry Sdn. Bhd. The study arises from the need to know the factors that can affect the OCB. This study is utilizing the quantitative approach and data collection was solely on questionnaire. The sampling of data collection is based on Zun Utara Industry Sdn. Bhd., the manufacturer of chest freezer and bottle cooler. Work engagement was measured with 10-items. POS was measured with 8-items. OCB was measured with 10-items. All dimensions were measured with Five Point Likert Scale. A total of 80 sets pre-printed questionnaires was distributed, 76 sets questionnaires were returned and valid to process. The data was analyzed by using Statistical Package for Social Science (SPSS) version 19.0. Technique of data analysis used in this study including frequency analysis, descriptive analysis and reliability analysis. The Pearson Correlation was applied to test the hypotheses developed and investigate the correlation between independent variables and dependent variable. Besides, multiple regression analysis is conducted to analyze the relationship between independent variables and dependent variable. From the research finding, it provides better understanding of the factor influence the OCB in manufacturing sector. The findings revealed that work engagement was statistically and significantly affect to OCB. Some of the recommendations for future research have been provided for improvement